2014
DOI: 10.1021/nn501871d
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanomatryoshkas as Efficient Near-Infrared Photothermal Transducers for Cancer Treatment: Benchmarking against Nanoshells

Abstract: Au nanoparticles with plasmon resonances in the near-infrared (NIR) region of the spectrum efficiently convert light into heat, a property useful for the photothermal ablation of cancerous tumors subsequent to nanoparticle uptake at the tumor site. A critical aspect of this process is nanoparticle size, which influences both tumor uptake and photothermal efficiency. Here, we report a direct comparative study of ∼90 nm diameter Au nanomatryoshkas (Au/SiO2/Au) and ∼150 nm diameter Au nanoshells for photothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
315
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 342 publications
(330 citation statements)
references
References 42 publications
6
315
0
Order By: Relevance
“…(34,35) A detailed explanation of the synthesis of the gold nanomatryoshkas can also be found in recent literature. (28,29) …”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…(34,35) A detailed explanation of the synthesis of the gold nanomatryoshkas can also be found in recent literature. (28,29) …”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…One promising approach in cancer treatment is the use of gold-based nanostructures, whose strong optical absorption is due to their plasmon resonance, to provide safe and effective light-based therapeutics. Plasmonic nanostructures are advantageous due to their unique optical properties, low toxicity, in vivo stability, and enhanced tumor uptake (4)(5)(6)(7)(8)(9)(10). One approach uses near-infrared (IR) light to heat silica core-gold shell nanoshells (NS) photothermally to locally ablate tumors, which has been shown to lead to tumor remission in mice at rates above 90% (11)(12)(13).…”
mentioning
confidence: 99%
“…In general, solid structures have higher scattering efficiencies than hollow ones which means that there is less energy available to convert into heat in photothermal applications [15,29,158,213,214]. For example, it has been reported that silica-gold core-shell nanoparticles (150 nm diameter) had total extinctions that are comprised of only 15% absorption efficiency [215]. Shells also have broadened spectral line widths due to variation in size and shape within an ensemble and are considered cytotoxic due to the polymer core [190,216].…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%